2019
DOI: 10.3390/molecules24061067
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Μetabolomics of the Lipid Fraction of Organic and Conventional Bovine Milk

Abstract: Origin and quality identification in dairy products is an important issue and also an extremely challenging and complex experimental procedure. The objective of the present work was to compare the metabolite profile of the lipid fraction of organic and conventional bovine milk using NMR metabolomics analysis. 1H-NMR and 1D TOCSY NMR methods of analysis were performed on extracted lipid fraction of lyophilized milk. For this purpose, 14 organic and 16 conventional retail milk samples were collected monthly, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…The assignment of the minor components of fat milk reported in Table 1, along with the experimental measured chemical shifts and some of the other principal resonances, was performed according to the available literature data, [20,24,27], 13 C-NMR data (full spectrum in Figure S2), and 2D spectroscopy (TOCSY full spectrum in Figure S3 and HSQC experiments in Figures S4 and S5). The minor components identified were CLA, caproleic acid (C10:1 cis-9), diacylglycerols (DAGs), linoleic acid, and linolenic acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assignment of the minor components of fat milk reported in Table 1, along with the experimental measured chemical shifts and some of the other principal resonances, was performed according to the available literature data, [20,24,27], 13 C-NMR data (full spectrum in Figure S2), and 2D spectroscopy (TOCSY full spectrum in Figure S3 and HSQC experiments in Figures S4 and S5). The minor components identified were CLA, caproleic acid (C10:1 cis-9), diacylglycerols (DAGs), linoleic acid, and linolenic acid.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the lipid profile of milk and dairy products has been studied by high-resolution NMR spectroscopy for differentiating the animal provenience [20][21][22][23], while other studies reported the presence of different CLA isomers [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…(b) It allows the unequivocal identification and quantification of minor analytes even in strongly overlapped spectral regions, and thus, it is of importance in the emerging field of lipidomics [ 56 , 57 , 58 , 59 , 60 , 61 ], provided that a spectrometer with 1 H resonance frequency ≥600 MHz is used.…”
Section: Discussionmentioning
confidence: 99%
“…Conjugated linoleic acids (CLAs) have been extensively investigated using 1 H- and 13 C-NMR [ 6 , 18 , 19 , 20 , 21 , 22 ]. NOESY experiments, and the analyses of spin–spin coupling constants were utilized to identify the geometric configurations of the double bonds [ 23 ].…”
Section: Introductionmentioning
confidence: 99%